Enterotype Bacteroides Is Associated with a High Risk in Patients with Diabetes: A Pilot Study - Jiajia Wang; Wenjuan Li; Chuan Wang; Lingshu Wang; Tianyi He; Huiqing Hu; Jia Song; Chen Cui; Jingting Qiao; Li Qing; Lili Li; Nan Zang; et al. (Journal of Diabetes Research)
Background. More and more studies focus on the relationship between the gastrointestinal microbiome and type 2 diabetes, but few of them have actually explored the relationship between enterotypes and type 2 diabetes. Materials and Methods. We enrolled 134 patients with type 2 diabetes and 37 nondiabetic controls. The anthropometric and clinical indices of each subject were measured. Fecal samples of each subject were also collected and were processed for 16S rDNA sequencing. Multiple logistic regression analysis was used to determine the associations of enterotypes with type 2 diabetes. Multiple linear regression analysis was used to explore the relationship between lipopolysaccharide levels and insulin sensitivity after adjusting for age, BMI, TG, HDL-C, DAO, and TNF-α. The correlation analysis between factors and microbiota was identified using Spearman correlation analysis. The correlation analysis between factors was identified using partial correlation analysis. Results. Gut microbiota in type 2 diabetes group exhibited lower bacterial diversity compared with nondiabetic controls. The fecal communities from all subjects clustered into two enterotypes distinguished by the levels of Bacteroides and Prevotella. Logistic regression analysis showed that the Bacteroides enterotype was an independent risk factor for type 2 diabetes by decreasing insulin sensitivity. The levels of lipopolysaccharide and tumor necrosis factor-alpha were higher in the Bacteroides enterotype compared to the Prevotella enterotype. Partial correlation analysis showed that lipopolysaccharide was closely associated with diamine oxidase, tumor necrosis factor-alpha, and Gutt insulin sensitivity index after adjusting for multiple covariates. Furthermore, the level of lipopolysaccharide was found to be an independent risk factor for insulin sensitivity. Conclusions. We identified two enterotypes, Bacteroides and Prevotella, among all subjects. Our results showed that the Bacteroides enterotype was an independent risk factor for type 2 diabetes, which was due to increased levels of lipopolysaccharide causing decreased insulin sensitivity.